Improving Understanding Of Simplex Operations Through Developing The Simplex Solver Application In Linear Program Courses - Sina, Ibnu; Ahmadi (Integral (Jurnal Penelitian Pendidikan Matematika), 2023)
Based on the researcher's experience, in Linear Program lectures there is a tendency for students to be less active so that the spirit in the learning process seems to be absent. In solving problems, students tend to follow the completion steps outlined by the lecturer. This may be due to the low ability of students to make mathematical models. One of the factors causing the low ability to make mathematical models is the limited teaching materials according to student abilities. One of the efforts that can be made to increase the ability to make mathematical models in the Linear Program course is to develop a Simplex Solver application that is suitable for student conditions. The purpose of developing the Simplex Solver application is for students to feel the convenience of studying Linear Programming courses so that the objectives of this course can be achieved. This type of research is development research. Data collection used by means of validation, observation, questionnaires, interviews and tests. Validation is carried out to determine the validity of the Simplex Solver application development. Observations, questionnaires and interviews were conducted to find out the practicality of developing the Simplex Solver application. The test was conducted to find out whether the development of the Simplex Solver application could improve the mathematical representation skills of Mathematics Education students at Pancasakti University, Tegal